Sorption and Degradation Capacity of Natural Estrogens in Freshwater Environmental System in Japan - Desmiarti, Reni; Li, Fu-Sheng (Journal of Engineering and Technological Sciences, 2011)
The  sorption  and  the  degradation  capacity  of  natural  estrogens  in freshwater  environmental  system  in  Japan  were  performed.  Batch  experiments were examined in water-sediment suspensions using six layers of sediment under aerobic and anaerobic conditions. The results indicated that the water-sediment partition coefficient of E1 (KdE1) was higher than E2 (KdE2). The degradation rate of E1 (kE1) was smaller than E2 (kE2). Under aerobic and anaerobic conditions, E1  was  formed  from  E2.  The  degradation  rate  of  E2  (kE2)  from  the  surface  to bottom of sediment layers was estimated fell in the range from 0.114 to 0.026 h-1 and 0.05 to 0.014 h-1  under aerobic and anaerobic conditions, respectively.